Label-free enrichment and molecular characterization of viable circulating tumor cells from diagnostic leukapheresis products - Franken, André; Endris, Volker; Stenzinger, Albrecht (Clinical chemistry, 2019)
INTRODUCTION: Circulating tumor cells (CTCs) may be used to improve cancer diagnosis, prognosis, and treatment. However, because knowledge regarding CTC biology is limited and the numbers of CTCs and CTC-positive cancer patients are low, progress in this field is slow. We addressed this limitation by combining diagnostic leukapheresis (DLA) and microfluidic enrichment to obtain large numbers of viable CTCs from metastasized breast cancer patients. - METHODS: DLA was applied to 9 patients, and 7.5 mL of peripheral blood was drawn. CTCs were enriched with the Parsortix™ system. The quality of CTCs from fresh and cryopreserved DLA products was tested, and CTCs were cultured in vitro. Single uncultured and cultured CTCs were isolated by micromanipulation to determine different parameters, such as genomic aberrations and mutation profiles of selected tumor-associated genes. Expression levels of estrogen receptor and HER2/neu were monitored during in vitro culture. - RESULTS: Viable CTCs from peripheral blood and fresh or frozen DLA products could be enriched. DLA increased the likelihood of successful CTC culture. Cryopreserved DLA products could be stored with minimal CTC loss and no overt reduction in the tumor cell quality and viability during an observation period of up to 3 years. The analyzed parameters did not change during in vitro culture. DLA samples with high CTC numbers and lower ratios of apoptotic CTCs were more likely to grow in culture. - CONCLUSIONS: The increased CTC numbers from fresh or cryopreserved DLA products facilitate multiple functional and molecular analyses and, thus, could improve our knowledge of their biology.
Published March 2019
Gesehen am 13.05.2019